Erratum: Prenatal and postnatal supplementation with lipid-based nutrient supplements reduces anemia and iron deficiency in 18-month-old Bangladeshi children: A cluster-randomized effectiveness trial - Matias, Susana L; Mridha, Malay K; Young, Rebecca T; Khan, Md Showkat A; Siddiqui, Zakia; Ullah, Md Barkat; Vosti, Stephen A; Dewey, Kathryn G (Oxford Academic, 2022)
This article was published in The Journal of Nutrition [Copyright © American Society for Nutrition 2019. This article is published and distributed under the terms of the Oxford University Press, Standard Journals Publication Model (https://academic.oup.com/journals/pages/open_access/funder_policies/chorus/standard_publication_model)] and the definite version is available at: https://doi.org/10.1093/jn/nxy221. The Journal's website is at: https://academic.oup.com/jn/article/149/7/1294/5523909